INTERACTION OF SYNDEMIES AND FASHION – PRESENTATIONS IN THE SECOND HALF OF THE XX CENTURY – THE BEGINNING OF THE XXI CENTURY - Kvasnytsia Rоksoliana (International Journal of Innovative Technologies in Social Science, 2022)
The purpose of this article is a selective overview of the concepts and approaches that have been used in the fashion industry as a result of the synergy of fashion and epidemics/pandemics. To outline the development strategy of one of the most important segments of the advertising campaign of fashion brands - the presentation of fashion collections, an analysis of the interaction of syndemic, social epidemics, pandemic Covid-19 and fashion, taking into account various aspects, namely: which epidemics/pandemics affected the presented fashion collections; positive and negative aspects of interaction; how the epidemic/pandemic affects the modernization of presentation spaces and spreading fashion trends. In addition to assessing the current situation, the article seeks to outline areas for future research. The interaction of social syndemies and fashion in various aspects, in particular, the impact on the design of the presentation space, deserves further research.